ACUTE ASCENDING MEDIASTINITIS AND NECK PHLEGMON CAUSED BY PANCREATIC PSEUDOCYST: CASE REPORT - Ilić, Bojan (Acta medicae Medianae, 2025)
Acute mediastinitis is one of the most severely known infections with high mortality rate. Mediastinitis occurs most commonly as a descending infection, spreading from oral cavity or pharynx. The most common thoracic complications of pancreatic disease are reactive pleural effusion and pneumonia, while rare complications include pancreaticopleural fistula with massive pleural effusion or hemothorax and extension of pseudocyst into the mediastinum. Only 50 cases of mediastinal extension of pancreatic pseudocyst have been published in the last 75 years with only one case of neck involvement reported. We report a case of acute respiratory distress syndrome followed by toxic enzymatic hydropneumothorax, mediastinitis and neck phlegmon caused by pancreatic pseudocyst fistula in 45 years old man. After initial diagnostics emergency operation was performed by multidisciplinary team. Ascending mediastinitis caused by pancreatic pseudocyst required a prompt surgical intervention. Early detection and an aggressive approach are crucial. Treatment should include surgical debridement and broad-spectrum antibiotics followed by adequate supportive care.